2009
DOI: 10.1172/jci40093
|View full text |Cite
|
Sign up to set email alerts
|

Nonpathogenic SIV infection of African green monkeys induces a strong but rapidly controlled type I IFN response

Abstract: African green monkeys (AGMs) infected with the AGM type of SIV (SIVagm) do not develop chronic immune activation and AIDS, despite viral loads similar to those detected in humans infected with HIV-1 and rhesus macaques (RMs) infected with the RM type of SIV (SIVmac). Because chronic immune activation drives progressive CD4 + T cell depletion and immune cell dysfunctions, factors that characterize disease progression, we sought to understand the molecular basis of this AGM phenotype. To this end, we longitudina… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

44
487
4
3

Year Published

2010
2010
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 338 publications
(551 citation statements)
references
References 55 publications
44
487
4
3
Order By: Relevance
“…African green monkeys, which are considered to be the natural host of SIVagm, will not progress to AIDS even though they show high viral loads upon SIV infection. Jacquelin et al 27 reported a strong type I IFN response in the acute phase of infection in the African green monkey, but immune activation was controlled during chronic infection, a response that differed from that of the rhesus macaques. In addition, our study also showed that pDC activation is highly correlated with disease pathogenesis in SIVmac239 infection, as the macaques in the late phase of infection had higher pDC activation compared with the chronic infected macaques.…”
Section: Discussionmentioning
confidence: 99%
“…African green monkeys, which are considered to be the natural host of SIVagm, will not progress to AIDS even though they show high viral loads upon SIV infection. Jacquelin et al 27 reported a strong type I IFN response in the acute phase of infection in the African green monkey, but immune activation was controlled during chronic infection, a response that differed from that of the rhesus macaques. In addition, our study also showed that pDC activation is highly correlated with disease pathogenesis in SIVmac239 infection, as the macaques in the late phase of infection had higher pDC activation compared with the chronic infected macaques.…”
Section: Discussionmentioning
confidence: 99%
“…However, there are major differences compared with SIVmac infection in macaques: the levels of several cytokines, including IFN-a, are lower than those observed during acute SIVmac infection, which is not due to a functional defect in the ability of pDCs to sense the virus [188,189]. Indeed, the TLR7/TLR9/IRF7 pathway is functional [188,189].…”
Section: Spontaneous Control Of Chronic Inflammation In Hiv/siv Infecmentioning
confidence: 99%
“…Indeed, the TLR7/TLR9/IRF7 pathway is functional [188,189]. In addition, natural hosts preserve their TH17 cells, and their epithelial barriers are not damaged and consequently they show no signs of microbial translocation.…”
Section: Spontaneous Control Of Chronic Inflammation In Hiv/siv Infecmentioning
confidence: 99%
“…Au contraire, chez l'AGM infecté par le SIVagm, la production de ces cytokines est globalement modérée [6]. Toutefois, une augmentation significative d'IFN-est observée dans les premières semaines de l'infection [8,9]. L'activité biologique des interférons se traduit par l'induction de l'expression de gènes appelés ISG pour IFN stimulated genes.…”
Section: Le Modèle Non Pathogène Des Singes D'afriqueunclassified
“…L'activité biologique des interférons se traduit par l'induction de l'expression de gènes appelés ISG pour IFN stimulated genes. Nous avons récemment montré que les ISG sont fortement induits et de manière identique pendant la phase aiguë de l'infection SIV chez l'AGM et chez le macaque (Figure 1D) [9]. Mais, alors que l'expression de ces gènes reste élevée dans les cellules du sang et des ganglions lymphatiques chez le macaque, elle décroît jusqu'à son niveau basal chez l'AGM dès la fin de la phase aiguë (4 semaines post-infection).…”
Section: Le Modèle Non Pathogène Des Singes D'afriqueunclassified